1993
DOI: 10.1017/s0140525x0003123x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural learning

Abstract: This target article presents a theory of human cultural learning. Cultural learning is identified with those instances of social learning in which intersubjectivity or perspective-taking plays a vital role, both in the original learning process and in the resulting cognitive product. Cultural learning manifests itself in three forms during human ontogeny: imitative learning, instructed learning, and collaborative learning – in that order. Evidence is provided that this progression arises from the developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
1,070
2
49

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,864 publications
(1,164 citation statements)
references
References 190 publications
18
1,070
2
49
Order By: Relevance
“…First, at the neural level, the social learning community (see Hurley & Chater 2005) has hailed as highly significant the discovery of "mirror neurons" in the prefrontal cortex of monkeys, which activate both when the monkey observes a specific goal-directed hand action, such as grasping an object, and also when the monkey performs that same action Rizzolatti et al 1996). This match between observation and execution of motor actions has led some researchers to suggest that the mirror-neuron system forms the basis both for imitation (Meltzoff & Decety 2003;Rizzolatti et al 2002;Williams et al 2001), which is one possible cultural transmission mechanism, and for theory of mind (Gallese & Goldman 1998), which has also been argued to be important in human cultural transmission (Tomasello 1999;Tomasello et al 1993).…”
Section: Evolutionary Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…First, at the neural level, the social learning community (see Hurley & Chater 2005) has hailed as highly significant the discovery of "mirror neurons" in the prefrontal cortex of monkeys, which activate both when the monkey observes a specific goal-directed hand action, such as grasping an object, and also when the monkey performs that same action Rizzolatti et al 1996). This match between observation and execution of motor actions has led some researchers to suggest that the mirror-neuron system forms the basis both for imitation (Meltzoff & Decety 2003;Rizzolatti et al 2002;Williams et al 2001), which is one possible cultural transmission mechanism, and for theory of mind (Gallese & Goldman 1998), which has also been argued to be important in human cultural transmission (Tomasello 1999;Tomasello et al 1993).…”
Section: Evolutionary Ecologymentioning
confidence: 99%
“…Third, if neuronal studies have been largely restricted to monkeys and whole-brain studies to adult humans, it is research at the cognitive level regarding social learning in great apes and, more recently, human children that has generated the richest current taxonomies of cultural learning, delineating such processes as program-level imitation, emulation, and affordance learning (Byrne & Russon 1998;Tomasello et al 1993;Want & Harris 2002;Whiten & Ham 1992;Whiten et al 2004). Cognitive models that seek to explain how these operate have begun to proliferate but remain few and quite crude in comparison to our understanding of genetic transmission mechanisms; they include Meltzoff and Moore's (1997) active intermodal matching (AIM), Heyes's (2005) associative sequence learning (ASL), and Byrne's (1999) string parsing models.…”
Section: Evolutionary Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…They copy people's actions on objects (Meltzoff, 1988b), suggesting that the unit for imitation, as it were, has now expanded to a person-thing relation, rather than solely body movements themselves. The development of object-directed imitation dovetails with the emergence of other behaviors at about this age, which also use people's actions to "refer" to attributes and affordances of objects (Butterworth, 1991;Tomasello et al, 1993;Trevarthen & Hubley, 1978), particularly the phenomenon of "social referencing" (Campos & Stenberg, 1981). By 18 months of age, it has been found that infants will imitate not only an adult's actual actions but the actions he or she intends or tries to produce, even if they are not fully realized; at this age, infants can now read below the surface behavior of the adult and reenact the goals, aims, or intentions of the adult (Meltzoff, 1994).…”
Section: Memory Representation and Developmental Change In Imitationmentioning
confidence: 99%
“…Many investigations have targeted this "efficiency blindness", and researchers argued that early imitation is a blind and automatic copying process (Tomasello et al 1993) that reflects the immaturity of causal understanding in infants (Dijksterhuis and Bargh 2001). In contrast, presuming a mentalistic interpretive stance in infants, others argue that infants attribute different goals and intentions to the demonstrator depending on their physical constraints (Bekkering et al 2000;Carpenter et al 2002).…”
Section: Introductionmentioning
confidence: 99%